2009
DOI: 10.1111/j.1471-6712.2008.00623.x
|View full text |Cite
|
Sign up to set email alerts
|

Conditions for successfully implementing resident‐oriented care in nursing homes

Abstract: This study reports an investigation of the conditions for a successful introduction of a resident-oriented care model on six somatic and psychogeriatric intervention wards in three Dutch nursing homes. This study aims to answer the following research question: 'What are the conditions for successfully implementing resident-oriented care?' To answer the research question, the organisational change process was monitored by using the '7-S' model of Peters and Waterman as a diagnostic framework. Based on this mode… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
21
0

Year Published

2013
2013
2018
2018

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 15 publications
(24 citation statements)
references
References 17 publications
3
21
0
Order By: Relevance
“…Reflecting on the question of what had contributed to the improvement of daily activities and the development of cultural values associated with person-centred care, this research largely confirms that of earlier research [6,9,13,14,51]. The promotion of dialogue, participation and influence of the staff during every phase of the project, joint decision-making and continuous appreciative and adaptive facilitation all contributed to transformational change.…”
Section: Discussionsupporting
confidence: 73%
See 2 more Smart Citations
“…Reflecting on the question of what had contributed to the improvement of daily activities and the development of cultural values associated with person-centred care, this research largely confirms that of earlier research [6,9,13,14,51]. The promotion of dialogue, participation and influence of the staff during every phase of the project, joint decision-making and continuous appreciative and adaptive facilitation all contributed to transformational change.…”
Section: Discussionsupporting
confidence: 73%
“…A complexity approach modifies the value of a detailed and realistic plan of change, which Berkhout et al [6] thought important for transformation towards a culture change facility, and offers an explanation for the co-evolution of the daily activities and the context through which this process of change took place. This indicates that development towards a culture change facility should begin somewhere, and on a small scale as is also suggested by Shield et al [53], instead of waiting for more ideal conditions for change or a certain organisational readiness, which according to Manley et al [33] is a favourable factor in the realisation of an effective workplace culture.…”
Section: Discussionmentioning
confidence: 98%
See 1 more Smart Citation
“…(2005)Quality of life instruments used in dementiaZwakhalen, Hamers, and Berger (2007)A behavioural pain scaleAchterberg, Pot, Scherder, and Ribbe (2007)The nottingham health profileGerritsen et al. (2008)The MDS challenging behaviour profileMcCool, Jogerst, Daly, and Xu (2009)Multidisciplinary reportsCooper, Maxmin, Selwood, Blanchard, and Livingston (2009)The Modified Conflict Tactics ScaleBerkhout, Boumans, Mur, and Nijhuis (2009)“7‐S” modelAcierno et al. (2010)The National Elder Mistreatment StudyTriemstra, Winters, Kool, and Wiegers (2010)The consumer quality index long‐term careInspectie voor de Gezondheidszorg, (2010)VrijheidsbeperkingHeidstra‐Wolke (2011)Zelf‐check voor verpleeghuisartsenPillemer et al.…”
Section: Table A1mentioning
confidence: 99%
“…Especially the supervisors' role was crucial for a successful implementation. The study had a one-group pre-test versus post-test design [35]. A study into residents' sedative drug utilization showed that the use of pro re nata medicines was strongly determined by the characteristics of the ward (unit) the patients lived in, not so much by institutional characteristics [36].…”
Section: Discussionmentioning
confidence: 99%